Sexual Gratification As A Serious Threat In Modern Criminal Reasoning On Aspects Of Judges' Considerations In Court Judgment - Muhamad Iqbal; Susanto; Bhanu Prakash Nunna (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Objective: This research aims to examine and analyze the problem of sexual gratification as a serious threat in modern criminal reasoning. Methodology: In this research, the authors used a normative juridical method. This method was employed to examine many types of legal materials by referring to diverse norms found in legislation and encompassing several related legal principles, history, doctrine, and jurisprudence. Thus, this method applied a statutory approach. Finding: Over time, since all kinds of gifts within the scope of gratification have developed, the segmentation has become wider. This suggests that valuable facilities and objects are not only money and luxury facilities but also anything that can facilitate all kinds of individual biological needs, such as sexual. Sexual gratification, which originated from prohibited activities against the law with different scopes, such as prostitution, has now been targeted as a gift in the form of sexual facilities as an effort or reward for prohibited services provided by legal subjects in the Corruption Eradication Law. In relation to several things, in this aspect, the regulation in practice still has difficulty enforcing the law on the issue of gratification, considering the difficulty of providing evidence in the regulation. As such, an alternative step in this aspect is to find a legal breakthrough, one of which is using the judge's authority at the examination stage. As happened in Court Judgment Number 87/PID.SUS/TPK/2013/PN.BDG, the fact was discovered that one of the witnesses in court stated that the Defendant asked for sexual services every Thursday or Friday night, but this was not considered in legal considerations. In fact, her statement should have been used as evidence against the Defendant. For this reason, modern criminal reasoning in the form of adjustments to the development of sexual gratification crimes is an effort to protect the nation. In arrangements relating to gratuities, there is a context relating to